Preparation and application of soy protein isolate-filled sucrose composite particles in sugar-reduced chocolate via protein-mediated morphological modulation - Yanke Wang; Sizhe Dong; Jinmei Wang; Jian Guo; Xiaoquan Yang (Food Research International, 2026)

Boosting low-temperature activity and thermal stability in light alkane oxidation by balancing confined Ru species and the MFI zeolite microenvironment - Jingjing Wang; Lianghui Xia; Yanfei Jian; Qiyuan Liu; Yujie Liu; Yani Wu; He Xu; Yaruo Zhao; Jingyao Wang; Zeyu Jiang; Jinghang Huo; Yanke Yu; et al. (Chemical Engineering Journal, 2026)

Microbial co-occurrence network and spatial metabolism underlie wheat cultivar effects on medium-high temperature Daqu fermentation - Yanke Shi; Hongkui He; Mengyao Niu; Yijun Fan; Miao Yu; Yesheng Ma; Peng Wang; Zengming Gao; Xiaoxue Chen (Food Research International, 2026)

Hydrothermal dynamics evolution of dry-hot valleys under multiple impacts - Yuankun Wang; Weiguo Ma; Yang You; Lei Zhao; Yanke Zhang; Dong Wang (Journal of Environmental Management, 2026)

Defect and multi-interface synergistic engineering of a sulfide heterostructure with spatially separated redox sites enabling efficient and stable photocatalytic H2 evolution - Yachong Wang; Chaoyue Zheng; Youlin Wu; Qingyang Pang; Yanke Yang; Jihuai Wu; Meihua Xin; Cheng Peng; Jiamin Lu; Yiming Xie (Chemical Engineering Journal, 2026)

ZNF200 and DDX17 regulatory loop promotes tumor growth and metastasis by activating RBPJ transcription in non-small cell lung cancer - Yanke Zhang; Hongbin Zhu; Xueqin Wang; Wei Dong; Maoyu Zhang; Xinyue Song; Danye Han; Qian Chai; Xueyi Feng; Xiaozheng Wei; Hongyu Chen; Yonghuai Li; et al. (Science China Life Sciences, 2026)

Structural and dynamic insights into SPDT for phosphorus allocation in rice - Haitao He; Yan Liu; Jie Zhang; Xiaofeng Zheng; Lihuan Jiang; Zhangmeng Du; Jiaqi Zuo; Shuo Cao; Xuemei Peng; Zhiwen Zheng; Kun Li; Cuicui Shen; et al. (Science China Life Sciences, 2026)

Quantifying the drivers of river thermal regimes in the Hanjiang River Basin under climate change and reservoir construction - Lei Zhao; Yuankun Wang; Yang You; Sen Wang; Yixu Wang; Changqing Meng; Yanke Zhang; Dong Wang (Journal of Hydrology, 2026)

Long-term spatiotemporal heterogeneity and drivers of lake thermal dynamics in the Yangtze river basin - Yuankun Wang; Weiguo Ma; Jiaxin Tao; Yang You; Lei Zhao; Yanke Zhang; Dong Wang (Environmental Research, 2026)

Chickpea sourdough as a functional ingredient in gluten-free bread: Impact on quality attributes - Ruixue Jiang; Zimu Lin; Honghao Shi; Yan Wang; Yanke Wang; Qiang Yang (Food Hydrocolloids, 2026)

Unveiling river thermal regimes in the Yangtze river basin, China, with a hybrid deep learning model - Yang You; Yuankun Wang; Jiaxin Tao; Lei Zhao; Sen Wang; Yanke Zhang; Changqing Meng; Dong Wang (Journal of Environmental Management, 2026)

SlXTH1, a xyloglucan endotransglucosylase/hydrolase in halophyte Suaeda liaotungensis, negatively regulates Arabidopsis seed germination under salt stress - Jieqiong Song; Haoran Ding; Nuo Cheng; Xinxin Li; Yanke Lu; Hongfei Wang; Changping Li; Qiuli Li (Plant Science, 2025)

Corrigendum to “Main lipid sources affecting key aroma volatile compounds in Chinese native chicken” [Food Chemistry 474 (2025) 142990] - Yanji Chen; Yongli Wang; Yanke Wang; Na Luo; Richun Cai; Yang Yu; Xu Zhang; Jinmei Zhu; Guiping Zhao; Jie Wen; Huanxian Cui (Food Chemistry, 2025)

Main lipid sources affecting key aroma volatile compounds in Chinese native chicken - Yanji Chen; Yongli Wang; Yanke Wang; Na Luo; Richun Cai; Yang Yu; Xu Zhang; Jinmei Zhu; Guiping Zhao; Jie Wen; Huanxian Cui (Food Chemistry, 2025)

Synergistic construction of efficient heterojunction structures through vacancy engineering and nanoscale effects to enhance photodegradation efficiency - Qingyang Pang; Chaoyue Zheng; Youlin Wu; Xuan Wang; Yachong Wang; Yanke Yang; Teng Li; Canzhong Lu; Yiming Xie; Fuda Yu (Journal of Water Process Engineering, 2025)

Crosstalk Between the Nervous System and Colorectal Cancer - Xi Li; Chunshui Ye; Min Wang; Patrick Kwan; Xin Tian; Yanke Zhang (Neuroscience Bulletin, 2025)

Exploring of laccase-like nanozyme and membrane filters for efficient removal of tetracycline hydrochloride - Yun Wang; Dan Wang; Qixuan Mu; Yanke Zhai; Jun Hai; Yibing Ji; Ruijun Li (Chemical Engineering Journal, 2024)

Facile synthesis of Metal-Organic Framework/Chitosan cryogel as a robust Scavenger for Diclofenac sodium - Yanke Shi; Lijin Huang; Yu Bai; Lei Ouyang; Huiyu Zhao; Xinquan Wang; Qin Shuai (Chemical Engineering Journal, 2024)

The spatiotemporal evolution of dry (wet), cold (hot) and rainstorm whiplash events and their socioeconomic exposure - Changqing Meng; Zhihan Hu; Yue Li; Yuankun Wang; Yanke Zhang; Keying Liu (Urban Climate, 2024)

A forecasting method for corrected numerical weather prediction precipitation based on modal decomposition and coupling of multiple intelligent algorithms - Changqing Meng; Zhihan Hu; Yuankun Wang; Yanke Zhang; Zijiao Dong (Meteorology and Atmospheric Physics, 2024)

Role of ocean-atmosphere interaction in intraseasonal variability of summer rainfall over the Indo–Northwest Pacific - Yang Wang; Zhen-Qiang Zhou; Renhe Zhang; Yanke Tan (Climate Dynamics, 2024)

Transfer and risk assessment of fipronil in laying hen tissues and eggs - Zhiwei Wang; Ziyan Du; Yanke Shi; Peipei Qi; Shanshan Di; Huiyu Zhao; Xiaofeng Ji; Chunbo Lu; Xinquan Wang (Science of The Total Environment, 2024)

Investigating long-term changes in surface water temperature of Dongting Lake using Landsat imagery, China - Yuankun Wang; Jiaxin Tao; Lei Zhao; Shuhao Qin; Huifang Xiao; Yixu Wang; Dong Sheng; Yanke Zhang (Environmental Science and Pollution Research, 2024)

Long-term straw return enhanced crop yield by improving ecosystem multifunctionality and soil quality under triple rotation system: An evidence from a 15 years study - Runxia Huo; Jinlong Wang; Kunkun Wang; Yanke Zhang; Tao Ren; Xiaokun Li; Rihuan Cong; Jianwei Lu (Field Crops Research, 2024)

Comparison of two filter approaches for characterizing boreal summer intraseasonal oscillation - Yang Wang; Zhen-Qiang Zhou; Renhe Zhang; Yanke Tan (Atmospheric Research, 2024)

Identification of characteristic aroma compounds in chicken meat and their metabolic mechanisms using gas chromatography–olfactometry, odor activity values, and metabolomics - Yanke Wang; Li Liu; Xiaojing Liu; Yidong Wang; Weifang Yang; Wenjuan Zhao; Guiping Zhao; Huanxian Cui; Jie Wen (Food Research International, 2024)

Effect of morphology and simultaneous sulfation on Fe doped CeO2 for selective catalytic reduction of NO with NH3 - Jinxiu Wang; Yuqiu Liu; Xianfang Yi; Yanting Chen; Yanke Yu; Jinsheng Chen (Fuel, 2023)

Portable high-throughput multimodal immunoassay platform for rapid on-site COVID-19 diagnostics - Yanke Shan; Bin Wang; Huachuan Huang; Keding Yan; Wenzhi Li; Shouyu Wang; Fei Liu (Analytica Chimica Acta, 2023)

Spatiotemporal patterns of satellite precipitation extremes in the Xijiang River Basin: From statistical characterization to stochastic behaviour modelling - Qiumei Ma; Changming Ji; Lihua Xiong; Yi Wang; Chong‐Yu Xu; Yanke Zhang (International Journal of Climatology, 2021)
Given the threats from rainstorm events that have been intensified due to climate change, the investigation of heavy/extreme precipitation is attracting increasing attention. The investigation of extreme precipitation, with its restricted tools and data, is quite different from that of nonextreme precipitation. Satellite precipitation estimates (SPEs) are promising precipitation measurements due to fine spatial resolution. However, the spatiotemporal patterns of SPE extremes remain unclear. Therefore, this study attempted to systematically analyse the spatiotemporal patterns of extreme SPEs provided by the Tropical Rainfall Measurement Mission (TRMM) research product from statistical characterization to stochastic behaviour modelling. The statistical characterization was depicted using comprehensive extreme precipitation indices (EPIs), while the stochastic behaviour was modelled using the generalized Pareto distribution (GPD) to fit the ‘peak over threshold’ samples and employing the max‐stable process to fit the ‘block maximum’ samples (Max: annual 1‐day maximum, RX1day: monthly 1‐day maximum, and RX5day: monthly 5‐day maximum) of the TRMM data. The TRMM extremes were analysed across the Xijiang River Basin, China. The results of the statistical characterization revealed that compared with gauge precipitation, most TRMM EPIs were discovered to have higher temporal dynamic levels. Moreover, the spatial median of the return level for each return period derived from temporal TRMM extreme modelling with the GPD was lower than that from gauge extremes. The spatial dependence of Max in TRMM was weaker than that of either RX1day or RX5day, primarily due to different precipitation‐generating processes existing between two extreme events at annual scale compared with monthly scale. Each of the Max, RX1day, and RX5day in TRMM exhibited stronger spatial dependence than that in gauge extreme precipitation, maybe related to the area‐average‐based representation of the SPEs. These findings can enhance our insight into the spatiotemporal patterns of extreme satellite precipitation, which is beneficial for operational flood risk management.

A physiological model of granulopoiesis to predict clinical drug induced neutropenia from in vitro bone marrow studies: with application to a cell cycle inhibitor - Wenbo Chen; Britton Boras; Tae Sung; Yanke Yu; Jenny Zheng; Diane Wang; Wenyue Hu; Mary E. Spilker; David Z. D’Argenio (Journal of Pharmacokinetics and Pharmacodynamics, 2020)

Involvement of MEM1 in DNA demethylation in Arabidopsis - Yanke Lu; Jie Dai; Liu Yang; Yumei La; Shaoxia Zhou; Sheng Qiang; Qianqian Wang; Feng Tan; Yufeng Wu; Weiwen Kong; Honggui La (Plant Molecular Biology, 2020)

Paecilomyces variotii extracts (ZNC) enhance plant immunity and promote plant growth - Chongchong Lu; Haifeng Liu; Depeng Jiang; Lulu Wang; Yanke Jiang; Shuya Tang; Xuwen Hou; Xinyi Han; Zhiguang Liu; Min Zhang; Zhaohui Chu; Xinhua Ding (Plant and Soil, 2019)

Analysis of the DNA methylation patterns and transcriptional regulation of the NB-LRR-encoding gene family in Arabidopsis thaliana - Weiwen Kong; Bin Li; Qianqian Wang; Bin Wang; Xiaoke Duan; Li Ding; Yanke Lu; Li-Wei Liu; Honggui La (Plant Molecular Biology, 2018)

Influence of the South Pacific decadal variability on Southeast China rainfall during boreal autumn - Gang Li; Jiepeng Chen; Xin Wang; Yanke Tan (International Journal of Climatology, 2018)
Using observational data and numerical experiments, the decadal relationship between South Pacific and rainfall over southeastern China during boreal autumn is examined. In the observational analyses, it is found that the boreal autumn South Pacific shows significant decadal variability with a significant periodicity of 11–21 years from 1960 to 2000, which is an independent phenomenon in the whole Pacific. This South Pacific decadal variability can induce significant decadal variability of boreal autumn rainfall over southeastern China. When the boreal autumn South Pacific decadal variability is in its positive phase, less rainfall appears over the southeastern China, and vice versa. The possible physical mechanisms are further investigated. It is suggested that the negative sea surface temperature anomalies (SSTA) in the extratropical South Pacific associated with positive phase of South Pacific decadal variability could result in an anomalous anticyclone to the east of Australia. The cross‐equatorial flow over the Maritime Continent and tropical western Pacific is enhanced under the influence of this anomalous anticyclone, favouring the location of western Pacific subtropical high moving more eastwards and then leading to the formation of anomalous cyclone over western North Pacific. To the west flank of this anomalous cyclone is the significantly anomalous northerly, which is favourable for less rainfall over southeastern China. On the other hand, significant negative SSTA appears in the Maritime Continent and tropical western Pacific could cause anomalous sinking motion here, which can further induce anomalous sinking motion over southeastern China through two meridional cells extending from Maritime Continent to southeastern China with a common rising branch over the southern South China Sea, thus resulting in less rainfall over southeastern China. Numerical experiments confirm our observational results.

Remote impact of North Atlantic sea surface temperature on rainfall in southwestern China during boreal spring - Gang Li; Jiepeng Chen; Xin Wang; Xia Luo; Daoyong Yang; Wen Zhou; Yanke Tan; Hongming Yan (Climate Dynamics, 2018)

Error inhomogeneity in the computation of spherical mean displacement - Xuezhong Wang; Banghui Hu; Hong Huang; Ju Wang; Gang Zeng; Yanke Tan; Li Zou (Journal of Meteorological Research, 2017)

Relationship between RAGE gene polymorphisms and cardiovascular disease prognosis in the Chinese Han population - Jinxiong Gao; Liehua Deng; Ying Wang; Yanke Shi; Xiaohua Xiao; Xueou Zheng; Hao Ren; Dingli Xu (Molecular Genetics and Genomics, 2017)

Lentiviral Vector-Induced Overexpression of RGMa in the Hippocampus Suppresses Seizures and Mossy Fiber Sprouting - Ling Chen; Baobing Gao; Min Fang; Jie Li; Xiujuan Mi; Xin Xu; Wei Wang; Juan Gu; Bo Tang; Yanke Zhang; Zhihua Wang; Ao Zhan; et al. (Molecular Neurobiology, 2017)

Brittle mechanical characteristics of hard rock exposed to moisture - Guoqing Chen; Tianbin Li; Fan Guo; Yanke Wang (Bulletin of Engineering Geology and the Environment, 2017)

Association of Microtubule Dynamics with Chronic Epilepsy - Xin Xu; Yida Hu; Yan Xiong; Zhonggui Li; Wei Wang; Chao Du; Yong Yang; Yanke Zhang; Fei Xiao; Xuefeng Wang (Molecular Neurobiology, 2016)

New Insight into the Effect of Potassium on Commercial SCR Catalyst: Promotion of Thermal Stability - Yanke Yu; Xiaoran Meng; Jinsheng Chen; Jinxiu Wang; Yanting Chen (Water, Air, & Soil Pollution, 2015)

ENT1 Inhibition Attenuates Epileptic Seizure Severity Via Regulation of Glutamatergic Neurotransmission - Zucai Xu; Ping Xu; Yalan Chen; Jing Liu; Yanke Zhang; Yaodong Lv; Jing Luo; Min Fang; Jun Zhang; Jing Wang; Kewei Wang; Xuefeng Wang; et al. (NeuroMolecular Medicine, 2015)

A new method for calculating the wind speed distribution of a moving tropical cyclone - Banghui Hu; Xiuqun Yang; Yanke Ttan; Yongqing Wang; Yong Fan (Advances in Atmospheric Sciences, 2010)